Priming of delayed harvest soybean (Glycine max L. Merr.) seeds for quality improvement - Thant, Phyu Sin (2015)
Unfavorable weather condition causes delayed in harvesting of soybean seeds and consequently deteriorates seed quality. A study was undertaken at Universiti Putra Malaysia to investigate the potential seed priming treatments for seed quality improvement of delayed harvest soybean (Glycine max L. Merr.) seeds. AGS190, Cikurai, Willis and Deing cultivars were grown in the field for two consecutive years from 2013 to 2014. In year I, seeds were harvested at harvest maturity (HM), one week after HM (H1) and two weeks after HM (H2). In year II, the seeds were harvested at HM, H1 and three weeks after HM (H3). Polyethylene glycol (PEG) of 0, -0.8, -1.1 and -1.8 MPa and chitosan of 0, 0.25, 0.5 and 0.75% were used to prime the seeds. For seedling emergence in the field, seed priming treatments using PEG and chitosan with similar concentrations were used. Changes in catalase (CAT), peroxidase (POD) and superoxide dismutase (SOD) enzyme activities and malondialdehyde (MDA) level in delayed harvest seeds were detected during priming. Seed quality of AGS-190 in year I was lower than in year II. The weather condition of high precipitation prior and during harvesting in year I was unfavorable to seed quality of AGS-190. The percent germination of Cikurai, Willis and Deing were more than 90% in year I. However, it significantly reduced when seeds were harvested three weeks after harvest maturity in year II due to longer exposure to field condition beyond HM. Increase in percent germination, germination index, speed of germination and seedling vigor index occurred when the seeds were primed with -0.8 MPa PEG and 0.5% chitosan. Chitosan priming reduced mean germination time for all harvest dates. The 0.5% chitosan needed 5.28-5.7days while unprimed seeds took more time to germinate (5.71- 5.97days). Low concentration of chitosan (< 0.5%) improved seedling emergence percentage and emergence speed of soybean seeds. Seed priming with water also improved percent seedling emergence of seeds as well as chitosan and PEG priming. Antioxidant enzyme activities decreased with the time of harvest in both AGS-190 and Willis cultivars. Seed primed with 0.5% chitosan enhanced CAT and POD in all harvested seeds of AGS-190 in year I. Moreover, the 0.5% chitosan enhanced POD and SOD in both HM and H1 seeds of AGS-190 cultivar in year II. For Willis cultivar,CAT activity of all three harvested seeds were improved by 0.5% chitosan priming while -0.8MPa PEG enhanced CAT activity for HM and H1 seeds. The accumulation of MDA was reduced in primed seeds compared with unprimed seeds. The seed priming with water was also effective to reduce lipid peroxidation like 0.5% chitosan and -0.8MPa PEG. The study suggests that soybean seed quality has considerably declined when the seeds are harvested at three weeks after harvest maturity in wet and warm tropical environment. Large seeded cultivars are more susceptible to reduction in seed quality than small seeded cultivars and delaying one week after harvest maturity is enough to decline seed quality. Chitosan priming improves seed vigor of delayed harvest soybean seeds by reducing mean time needed for germination. Hydropriming with water also can improve seed quality as well as priming with chitosan and PEG.